Planning the qualitative research interview. - Whiteley, Alma; McCabe, Margaret; Buoy, Lynette; Howie, Fred; Klass, Des; Latham, J.; Bickley, Maureen; Luckeenarain, Leela (Graduate School of Business, Curtin University of Technology, 1998)
This working paper discusses a method for planning the qualitative research interview. The paper briefly considers the variety of purposes for which the interview is used and focuses on increasing the rigour of the investigative interview as a qualitative research technique. A range of dimensions which can be found in any number of interviews are described. A model is presented for dealing with the way in which these dimensions are taken into account in the planning of the qualitative interview. The research context is the determining factor in selecting which dimensions are to be focussed upon and when analysing the degree to which any one of them can impact on any given qualitative interview.